EKSTRAKULIKULER PIDATO DALAM MENUMBUHKAN KECERDASAN LINGUISTIK SISWA MADRASAH IBTIDAIYAH AN-NAJIHAH BABUSSALAM - Dyah Ayu Roiyani Sumaji; Dwi Rohman Soleh; Aris Wuryantoro (CV Edujavare Publishing, 2026)
This research is based on the importance of speech activities as a form of public speaking practice that plays a crucial role in improving students’ communication skills. Through speech extracurricular activities, students are trained to build self-confidence, improve pronunciation and intonation, and enrich their vocabulary and grammatical competence, all of which contribute to the development of linguistic intelligence. The purpose of this study is to describe the implementation of speech extracurricular activities at Madrasah Ibtidaiyah An-Najihah Babussalam, explain their role in fostering students’ linguistic intelligence, and identify the aspects of linguistic intelligence developed through these activities. This study employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation, and analyzed through data condensation, data presentation, and conclusion drawing. Data validity was ensured through persistence and triangulation. The results show that speech activities are implemented through structured stages, including role division, speech text preparation, rehearsal, and performance. These activities effectively enhance students’ reading comprehension, vocabulary mastery, writing ability, critical thinking, effective communication, public speaking skills, and attentive listening.